2019
DOI: 10.1080/1331677x.2019.1592007
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing innovative employees: effects of organisational learning and work environment

Abstract: The present study examines the effects of organisational learning and work environment on the formation of employees' innovative work behaviour. A stratified sampling technique was used for the sample of employees at micro and small-scale manufacturing enterprises located in selected cities of the East Coast Economic Region, Peninsular Malaysia. The authors' analysis revealed innovative work behaviour of micro and small manufacturing enterprises at a moderate level. Moreover, the innovative work behaviour at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 83 publications
0
19
1
Order By: Relevance
“…Previous studies by Sapie et al (2015), Awang et al (2014), Yunus et al (2014) and Hilmi et al (2012) concluded that the level of IWB of individuals in Malaysia remains at a moderate level. Furthermore, recent study by Awang et al (2019) found that the IWB at micro-enterprises is significantly lower than small enterprises.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies by Sapie et al (2015), Awang et al (2014), Yunus et al (2014) and Hilmi et al (2012) concluded that the level of IWB of individuals in Malaysia remains at a moderate level. Furthermore, recent study by Awang et al (2019) found that the IWB at micro-enterprises is significantly lower than small enterprises.…”
Section: Introductionmentioning
confidence: 96%
“…By conducting SEM analysis, Alikaj et al [33] confirmed that an employee's perception of thriving at work is highly related to his or her degree of creativity. Awang et al [34] emphasized the impact of individual learning through thriving at work on innovative behaviour. Given the above arguments, one would expect:…”
Section: Model Development 41 Thriving At Work and Innovative Behaviourmentioning
confidence: 99%
“…Further, when employees perceive a work environment that is characterized by a favourable learning climate and capable of dealing with mistakes, they are likely to develop knowledge through reflection and experimentation on their job and consequently become more innovative [10]. In addition, according to Awang et al [34], work environment is very important factor for employees' innovative work behaviour. On the other hand, bad organizational climate is main constraint to employee behaviours [50].…”
Section: Organizational Climate and Innovative Behaviourmentioning
confidence: 99%
“…These creativity dimensions are adopted from Lukes and Stephan (2017). Akram et al (2016) and Awang et al (2019) asserted that innovation is the key to success in an organization and good human capital management is a major factor in achieving high innovative capabilities. Oldham and Cummings (1996) indicated that creativity is at an individual stage, whereas innovation is at an organizational level.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%